School Bullying and its Relationship to Social Skills among Secondary School Students An Analytical Study (Comprehensive Journal of Science, 2026)
School bullying is a negative behavioral phenomenon that has become increasingly prevalent in educational institutions, particularly at the secondary level, due to a range of social, psychological, and educational factors. Bullying is characterized by repeated aggressive behavior by a student or group of students towards others, taking various forms such as verbal, physical, psychological, or social abuse. This negatively impacts the school climate and the students' mental and social well-being.The phenomenon of school bullying is closely linked to students' level of social skills. These skills are essential for individuals to interact positively with others, manage their emotions, and resolve conflicts constructively. Weak social skills increase the likelihood of engaging in or being subjected to bullying behaviors, resulting from an inability to communicate effectively or defend oneself positively.
Keywords: School bullying, social skills, secondary school students, school environment.